Realising the right to an adequate standard of living through the New Partnership for Africa's Development - Nsibirwa, Martin (University of Pretoria, 2006)
Prepared under the supervision of Mr. Martin Nsibirwa, Centre for Human Rights, Faculty of Law, University of Pretoria, South Africa